Simple solution for low cost bandwidth management - I Made Sukarsa; I Nyoman Piarsa; I Gede Bagus Premana Putra (Universitas Ahmad Dahlan, 2021)
Organizations in this era can't be separated from information technology, especially in communication and information sharing. The existence of information technology, especially computer networks, greatly facilitates agencies in terms of communication. Organizations that have used computer networks generally don’t have tools to handle security and bandwidth management issues in large numbers, resulting in wasteful use of bandwidth for unproductive purposes, such as accessing video streaming. The fact is professional tools to overcome the problem of security and bandwidth management issues are already in the market, but have hundreds of millions of priced. The high price of professional devices gave an opportunity to develop a bandwidth management system based on the integration of the remote authentication dial in user service (RADIUS) server and Mikrotik RouterBoard, at a lower cost. RADIUS server was chosen as a service for network security, because it supports the legal authentication for users via AAA protocol. The RADIUS server can be integrated with MySQL database, it can be developed SSO systems. Bandwidth management can be done with Mikrotik feature, but has the disadvantages of scalable storage, that problem can overcome by integrating Mikrotik and RADIUS server, then defining time doing data packet quota for the client and its implementation can help with hypertext preprocessor (PHP) scripts.